PENDIDIKAN KETAQWAAN DALAM AL-QUR’AN - Radhiatul Hasnah M (Murabby: Jurnal Pendidikan Islam, 2021)
Taqwa is the main principle of Islamic teaching which is the measure of human dignity before Allah. The most noble person in the sight of Allah is the most pious. Taqwa is born as a logical consequence of solid faith, faith that is always nurtured with murāqabatullāh, is afraid of the wrath of Allah's adzab, and always hopes for an abundance of His bounties and maghfirah. Taqwa is applied in the relationship between humans and God, namely the relationship between a creature and its Creator. The relationship between humans and God is a servile relationship characterized by obedience, obedience, and submission to Allah. The actualization of piety related to Allah in the process of education is the realization of an awareness of appreciation and practice of the values of trust and responsibility between teachers and students in their activities, based on the insight 'Indeed we belong to Allah, and only to Him alone. we are back” (to account for our educational charity.